El facebook y su incidencia en las relaciones familiares en los hogares del sector La Palmira del cantón Mocache - Alvarez Hidalgo, Edith Estefania (2020)
The present research on the Facebook and it´s impacto on family relations in households in the sector of the canton Mocache´s “La Palmira”, analyzes its consumption, and the campaign in which it affetcx the families of the aforementioned sector. Currently Facebook is one of the most used social networks, both in youth and in adults, because of its content and the various options to make in it, ranging from obtaining information about the daily events, upload photos, videos, until making video calls. The multiple functions of this network make people dedicate most of their time to be aware of it rather than their family, reaching the point of communicating through it even though they are in the same home. The following research shows that there are conflicts within households, due to the time of use that family members give to Facebook, leaving aside the physical interrelation between them.